2021
DOI: 10.3390/molecules26216501
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress and Application of Single-Atom Catalysts: A Review

Abstract: Due to excellent performance properties such as strong activity and high selectivity, single-atom catalysts have been widely used in various catalytic reactions. Exploring the application of single-atom catalysts and elucidating their reaction mechanism has become a hot area of research. This article first introduces the structure and characteristics of single-atom catalysts, and then reviews recent preparation methods, characterization techniques, and applications of single-atom catalysts, including their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 122 publications
(125 reference statements)
1
25
0
Order By: Relevance
“…To carry out the CO oxidation reaction, different strategies have been studied, the vast majority of which use an inorganic structure decorated with noble metals such as Pd, Pt, and Rh. [12][13][14][15][16][17][18][19] Among the most studied materials, cerium dioxide (CeO 2 ) stands out because of its excellent physicochemical properties, oxygen exchange capability, the possible creation of oxygen vacancies, and its redox characteristics. The application of ceria-based materials is determined by the electronic configuration of cerium and the high stability of its two valence states.…”
Section: Introductionmentioning
confidence: 99%
“…To carry out the CO oxidation reaction, different strategies have been studied, the vast majority of which use an inorganic structure decorated with noble metals such as Pd, Pt, and Rh. [12][13][14][15][16][17][18][19] Among the most studied materials, cerium dioxide (CeO 2 ) stands out because of its excellent physicochemical properties, oxygen exchange capability, the possible creation of oxygen vacancies, and its redox characteristics. The application of ceria-based materials is determined by the electronic configuration of cerium and the high stability of its two valence states.…”
Section: Introductionmentioning
confidence: 99%
“…A defect-rich surface can aid the stable anchoring of metal SAs on support. Chang et al researched the anchoring of Pt SAs to a TiO 2 (110) surface. [152] Their theoretical and experimental investigations revealed that among five different sites on TiO 2 available for Pt adsorption, basal V O s most strongly bind Pt SAs, improving the interaction between Pt and TiO 2 .…”
Section: Active Sites and Co 2 Adsorption/activationmentioning
confidence: 99%
“…Several studies have been conducted to understand and improve the interaction between catalysts and H 2 O molecules. For instance, Pertik et al investigated H 2 O adsorption on V O -rich rutile TiO 2 (110). [158] Their experimental and theoretical investigations revealed that V O s in TiO 2 dissociate H 2 O by transferring a proton to a neighboring oxygen atom, resulting in the formation of two hydroxyl groups at each vacancy.…”
Section: Role Of H 2 O Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the accumulation of active centers, their catalytic effect is often not as good as natural enzymes . Since single-atom (SAs) materials were reported, more and more researchers have been attracted by the high atom utilization and extraordinary catalytic performance of SAs, , and they are committed to developing the unique value of SA materials in electrocatalysis . Many studies have shown that the development of SA catalytic materials in electrochemical detection applications has obvious potential value .…”
Section: Introductionmentioning
confidence: 99%